A 12-Years Old Boy with Penetrating Scrotal Trauma grade III at Bhayangkara Hospital, Kupang, East Nusa Tenggara, Indonesia - Telussa, Arley Sadra; Wardana, I Gede Aprilian I; Purba, Julya Dasura (Cendana Medical Journal, 2023)
A 12-year-old boy was referred to the Emergency Room (ER) after experiencing penetrating trauma to his right scrotum caused by the iron of the bicycle seat. There were no urinary complains and the vital signs were good. Scrotal exploration was performed to repair the testicular trauma.